An Inverse polynomial integral

Calculus Level 3

1 x 6 + 3 x 4 + 3 x 2 + 1 d x = A π C B \int _{ -\infty }^{ \infty }{ \frac { 1 }{ { x }^{ 6 }+3x^{ 4 }+{ 3x }^{ 2 }+1 } dx } = \frac { A{ \pi }^{ C } }{ B }

The equation above holds true for positive coprime integers A A and B B . Find the value of A + B + C A+B+C .


The answer is 12.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Dec 27, 2019

By Residue Theorem: As suggested by @Syed Shahabudeen

I = d x x 6 + 3 x 4 + 3 x 2 + 1 = d x ( x 2 + 1 ) \begin{aligned} I & = \int_{-\infty}^\infty \frac {dx}{x^6+3x^4+3x^2+1} = \int_{-\infty}^\infty \frac {dx}{(x^2+1)} \end{aligned}

Using a big semicircular contour C C in the upper half complex plane, it will have length π R \pi R , but the integrand of the order 1 / R 3 1/R^3 , so this contribution from the big semicircle goes to zero on taking R R \to \infty . Then we have

I = C 1 ( z 2 + 1 ) 3 d z = C d z ( z + i ) 3 ( z i ) 3 Only pole z = i of z = ± i is enclosed by the contour. = 2 π i 2 ! [ d 2 d z 2 ( 1 ( z + i ) 3 ) ] z = i By Cauchy integral formula = 3 π 8 \begin{aligned} I & = \int_C \frac 1{(z^2+1)^3} dz \\ & = \int_C \frac {dz}{(z+i)^3(z-i)^3} & \small \blue{\text{Only pole }z=i \text{ of }z=\pm i \text{ is enclosed by the contour.}} \\ & = \frac {2\pi i}{2!} \left[\frac {d^2}{dz^2} \left(\frac 1{(z+i)^3} \right) \right]_{z=i} & \small \blue{\text{By Cauchy integral formula}} \\ & = \frac {3\pi}8 \end{aligned}

Therefore A + B + C = 3 + 8 + 1 = 12 A+B+C = 3+8+1 = \boxed{12} .

References:


By Beta and Gamma Functions: Similar solution with @Syed Shahabudeen's

I = = 1 x 6 + 3 x 4 + 3 x 2 + 1 d x Since the integrand is even = 2 0 d x ( x 2 + 1 ) 3 Let x = tan θ d x = sec 2 θ d θ = 2 0 π 2 sec 2 θ sec 4 θ d θ = 2 0 π 2 sin 0 θ cos 4 θ d θ Beta function B ( m , n ) = 2 0 π 2 sin 2 m 1 t cos 2 n 1 t d t = B ( 1 2 , 5 2 ) and B ( m , n ) = Γ ( m ) Γ ( n ) Γ ( m + n ) = Γ ( 1 2 ) Γ ( 5 2 ) Γ ( 3 ) where Γ ( ) denotes the gamma function. = Γ ( 1 2 ) 3 2 1 2 Γ ( 1 2 ) 2 ! From Γ ( 1 + s ) = s Γ ( s ) , Γ ( 1 2 ) = π = 3 π 8 and Γ ( n ) = ( n 1 ) ! \begin{aligned} I & = \int_{=\infty}^\infty \frac 1{x^6+3x^4+3x^2+1} dx & \small \blue{\text{Since the integrand is even}} \\ & = 2 \int_0^\infty \frac {dx}{(x^2+1)^3} & \small \blue{\text{Let }x = \tan \theta \implies dx = \sec^2 \theta \ d\theta} \\ & = 2 \int_0^\frac \pi 2 \frac {\sec^2 \theta}{\sec^4 \theta} d\theta \\ & = 2 \int_0^\frac \pi 2 \sin^0 \theta \cos^4 \theta d\theta & \small \blue{\text{Beta function }B(m,n) = 2\int_0^\frac \pi 2 \sin^{2m-1} t \cos^{2n-1} t\ dt} \\ & = B \left(\frac 12, \frac 52\right) & \small \blue{\text{and }B(m,n) = \frac {\Gamma(m)\Gamma(n)}{\Gamma(m+n)}} \\ & = \frac {\Gamma\left(\frac 12\right)\Gamma\left(\frac 52\right)}{\Gamma\left(3\right)} & \small \blue{\text{where }\Gamma (\cdot) \text{ denotes the gamma function.}} \\ & = \frac {\Gamma\left(\frac 12\right)\cdot \frac 32\cdot \frac 12 \Gamma\left(\frac 12\right)}{2!} & \small \blue{\text{From }\Gamma (1+s) = s\Gamma(s), \ \Gamma\left(\frac 12\right) = \sqrt \pi} \\ & = \frac {3\pi}8 & \small \blue{\text{and }\Gamma (n) = (n-1)!} \end{aligned}

Therefore A + B + C = 3 + 8 + 1 = 12 A+B+C = 3+8+1 = \boxed{12} .

References:

Neat and a beautiful solution ,sir. This question was actually asked in a kerala university exam and it was mentioned to solve the integral with the aid of Residue Theorem.

Syed Shahabudeen - 1 year, 5 months ago

Log in to reply

I see. I visited many years ago. Might have visited the university even.

Chew-Seong Cheong - 1 year, 5 months ago

@Syed Shahabudeen , managed to solve it by residue theorem

Chew-Seong Cheong - 1 year, 5 months ago

Log in to reply

Great sir, 👍😊.

Syed Shahabudeen - 1 year, 5 months ago
Syed Shahabudeen
Dec 26, 2019

Since the 6 degree polynomial is just an expansion of ( 1 + x 2 ) 3 \left( 1+{ x }^{ 2 } \right) ^{ 3 } . The following integral can be written as 1 ( 1 + x 2 ) 3 d x \int _{ -\infty }^{ \infty }{ \frac { 1 }{ { \left( 1+{ x }^{ 2 } \right) }^{ 3 } } } dx . Since the integrand is an even function. It can be written as 2 0 1 ( 1 + x 2 ) 3 d x 2\int _{ 0 }^{ \infty }{ \frac { 1 }{ { \left( 1+{ x }^{ 2 } \right) }^{ 3 } } } dx on substituting x = tan θ x = \tan \theta we get 2 0 π 2 sec 2 θ ( 1 + tan 2 θ ) 3 d θ 2\int _{ 0 }^{ \frac { \pi }{ 2 } }{ \frac { { \sec }^{ 2 }\theta }{ { \left( 1+{ \tan }^{ 2 }\theta \right) }^{ 3 } } } d\theta on simplifying we get 2 0 π 2 cos 4 θ d θ 2\int _{ 0 }^{ \frac { \pi }{ 2 } }{ { \cos }^{ 4 }\theta } d\theta By applying wallis formula for sine cosine special integrals. we'll get 2 0 π 2 cos 4 θ d θ = 2 ( 1 2 ( Γ ( 1 2 ) Γ ( 5 2 ) Γ ( 3 ) ) ) = 3 π 8 2\int _{ 0 }^{ \frac { \pi }{ 2 } }{ { \cos }^{ 4 }\theta } d\theta \quad =\quad 2\left( \frac { 1 }{ 2 } \left( \frac { \Gamma \left( \frac { 1 }{ 2 } \right) \Gamma \left( \frac { 5 }{ 2 } \right) }{ \Gamma \left( 3 \right) } \right) \right) =\frac { 3\pi }{ 8 } . Therefore we get A + B + C = 12 \boxed{A+B+C=12}

You need to mention it is "positive coprime integers" because negative ones work too. Then the answer can be 10 -10 . Use backslash in front for all functions like \int, therefore also \cos, \sin, \tan, \sec, \cot, \csc. Note that \cos x cos x \cos x cos is not italic because it is a function and not variable as x, which is a variable. Note also that there is a space between cos and x. Note that cos x c o s x cos x everything is italic and there is no space between cos and x.

Chew-Seong Cheong - 1 year, 5 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...